A financial evaluation of price formulae - J. J. Doppegieter; I. J. Lambrechts (South African Journal of Business Management, 1985)
This is the second in a series of four articles on price formulae/determination. In the first a simulation model was developed and the criterion of evaluating the model, the internal rate of return, was introduced. In this article two price formulae are simulated and analysed in accordance with principles discussed in the first article. Significant differences emerge between the two formulae. The internal rate of return of formula B (which is expressed in terms of replacement values) is continuously more than 100 % higher and more stable than that of formula A (which is expressed in terms of historical values). It also appears that it can be misleading to judge the profitability of a price formula against the allowed rate of profitability. The adequacy of the price formulae for inflation is judged by examining the internal rate of return in a situation with and without inflation and by calculating the ratio between depreciation allowed and replacement investments. Finally, the effect of the formulae on financial structure is analysed by calculating a liquidity (based on cash flow) and a solvability ratio. In conclusion, it appears that formula B is superior to formula A, mainly as a result of differences between the price formulae.
Keywords: 650